The Influence Of Financing To Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF) On The Profitability Of Islamic Commercial Banks Period 2019-2023 - Anggara Deno Putra; Indria Puspitasari Lenap (International Journal of Economics, Business and Innovation Research, 2025)
This research aims to identify the effect of FDR, CAR, and NPF on Profitability both partially and simultaneously at Islamic Commercial Banks in Indonesia for the 2019-2023 period. All Islamic commercial banks in Indonesia for the period 2019-2023 are selected for the population in this research. The sampling technique in this study used the Purpose Sampling method with the criteria of Islamic commercial banks registered with the OJK and issued financial reports (Annual Report) in 2019-2023. The secondary data are used in this research. The data analysis method in this study uses a panel data regression model using Eviews 10. The results show that FDR, CAR, and NPF have no partial effect on profitability. Simultaneously FDR, CAR, and NPF partially affect profitability.